2022
DOI: 10.3390/ani12091198
|View full text |Cite
|
Sign up to set email alerts
|

Olive Pomace and Soybean-Sunflower Acid Oils as Alternative Fat Sources in European Seabass (Dicentrarchus labrax) Diets: Effects on Performance, Digestibility and Flesh Fatty Acid Composition and Quality Parameters

Abstract: The effects of dietary inclusion of soybean-sunflower and olive pomace acid oils on growth, digestibility and flesh composition were studied in European seabass. Eight diets were fed for 100 days (101.37 ± 0.33 g initial weight, mean ± SD), differing in the added fat source (25% fish oil, 75% experimental oil): S (crude soybean oil), SA (soybean-sunflower acid oil), O (crude olive pomace oil) or OA (olive pomace acid oil); 3 blends: S-O, S-OA, SA-OA at a 1:1 ratio; and a diet containing only fish oil (F) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
3
4
1
Order By: Relevance
“…The aim of this work was to evaluate the effect of the partial replacement of FO in fish diets by AO instead of crude oils from two different vegetable sources (soybean and olive pomace) on lipid composition, oxidative stability, color, and sensory acceptance of fresh and refrigerated European seabass fillets. This study complements the information published by Verge-Mèrida et al [13] on growth and digestibility parameters of the same specimens used in the present work.…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…The aim of this work was to evaluate the effect of the partial replacement of FO in fish diets by AO instead of crude oils from two different vegetable sources (soybean and olive pomace) on lipid composition, oxidative stability, color, and sensory acceptance of fresh and refrigerated European seabass fillets. This study complements the information published by Verge-Mèrida et al [13] on growth and digestibility parameters of the same specimens used in the present work.…”
Section: Introductionsupporting
confidence: 90%
“…Remarkably, the recommendations published by FEDNA [27] for the use of AO in animal diets establish a total MIU value lower than 5%, which was fulfilled by the SAO and slightly exceeded by OPAO. In fact, in the performance parameters resulting from the experimental diets used in this work and that were reported by Verge-Mèrida et al [13], no effect was observed when SAO was used, but a significantly lower performance was found when fish were fed with OPAO diet, showing the lowest weight (226.22 g vs. the range of 244.45-250.20 g), specific growth rate (0.80%/day vs. the range of 0.88-0.90%/day), and average daily gain (1.25 g vs. the range of 1.43-1.49 g). Regarding the apparent digestibility of dry matter, crude protein, or total FA, no Aquaculture Nutrition effect was observed when AO were included in the diets [13].…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations